Management of Ischemic Colitis - Washington, Christopher; Carmichael, Joseph C. (Clinics in Colon and Rectal Surgery, 2012)
Ischemic colitis is a commonly misunderstood clinical condition. Although the colon is the most common region of ischemia in the gastrointestinal tract, many surgeons have difficulty with diagnosis and treatment of ischemic colitis. The process can occur from either occlusive vascular disease or nonocclusive disease, and can be gangrenous or nongangrenous. Differentiating gangrenous from nongangrenous disease can be a difficult clinical challenge as both sets of patients generally present with abdominal pain and bloody diarrhea. Although the majority of patients have transient ischemia with nongangrenous colitis that can be successfully managed nonoperatively, prompt recognition and surgical intervention is critical in patients with gangrenous colitis. In this article, the diagnosis and treatment of ischemic colitis is reviewed with emphasis on a systematic, evidence-based approach to management.
Keywords: ischemic colitis; gastrointestinal bleeding; colonoscopy; colectomy